Pemanfaatan Tools Live2D terhadap Animasi menggunakan Metode Face Tracking - Azhilla Margiani Saraswati; Iwan Rizal Setiawan; Asriyanik Asriyanik (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
In the era of globalization, cultural exchange is easier to do. One of the cultures that are popular with young people in Indonesia is Japanese animation. Animation is an image that is made to look real with artificial intelligence technology. At this time many people are interested in animated content that is displayed in real-time via social media, but there are still many who have not been able to present it optimally regarding the expressions and movements of the characters. So the researchers used the face tracking method in the Live2D application to produce animated characters that can interact directly with the exact expressions of the actors behind the camera. Tests using Vtube Studio Unity proved that the animations created succeeded in displaying the actors' expressions and movements in real-time. The final result of the animation created is distributed via social media YouTube and TikTok. Keywords: Animation, Live2D, Character, Face Tracking